Analisis Pengawet Nitrit Pada Daging Sapi Dengan Spektrofotometri Uv-Vis - Rusdi Rusdi; Zulharmita Zulharmita; Izzatus Salaafia Nurrohmah (STIFARM Padang, 2015)
The study about analysis of preservative sodium nitrite in beef by Spectrophotometry method has been done. The study was conducted by using which obtained from two supermarket and three traditional markets in Padang city, there are samples A, B, C, D and E. The levels of sodium nitrite in beef was determined by qualitative and quantitative analyzing. The result showed that preservative sodium nitrite found in samples A and B, which levels in samples A was 11,325 mg/Kg and samples B was 0,575 mg/Kg. While sodium nitrite was not found in samples C, D and E. It can be concluded that the levels of sodium nitrite in samples A and B are comply with requirements of Regulation of The Head of The National Agency of Drug and Food Control of Republic Indonesia No. 36 year 2013 which is concerning about food additives, which levels of preservative nitrite is maximum of 30 mg/Kg.